Disaster Property Insurance in Uzbekistan : Overview and Recommendations - World Bank (World Bank, Washington, DC, 2020)
This report was prepared at the request of the ministry of finance (MoF) and ministry of emergency situations of Uzbekistan as of February 2019. It aims to provide a detailed overview of the current status of disaster insurance for residential property in the country, identify gaps, and provide recommendations for a way forward. Uzbekistan is prone to many natural disasters that have a devastating potential for the economy and the population. It is widely recognized that disaster insurance can reduce the fiscal impact of natural disasters as well as their adverse economic impact on the population; and lead to a faster post-disaster recovery. Disaster insurance in Uzbekistan is offered by the private insurers. The Government of Uzbekistan (GoU) can consider the following actions to further strengthen disaster insurance: (i) establish a centralized disaster insurance national pool in the form of a public-private partnership; (ii) improve regulatory framework for disaster insurance; (iii) strengthen the insurance supervision of the disaster insurance market and introduce adequate reporting of catastrophe risk accumulations retained by insurance companies; and (iv) invest in better risk information systems. The report is structured in three main parts. The first part provides an overview of Uzbekistan disaster profile and buildings’ seismic vulnerability based on a risk assessment performed for the Kyrgyz Republic. The second part provides an overview of the local insurance market, disaster insurance line of business, and analyzes the current gaps in coverage and regulation. The third part reviews four examples of disaster insurance programs from the Kyrgyz Republic, Romania, Turkey, and New Zealand.